Bidmas

Oct 2005
299
1
Ok I was given this today:

6 - 2 x 4 + 3

Ok so if I use BIDMAS (Brackets Indices Division Multiplication Addition and Subtraction) I get

= 6 - 8 + 3
= 6 - 11
= -5

I was then told the answer was 1 which you get by doing

= 6 - 8 + 3
= -2 + 3
= 1

How come when using BIDMAS rule, which all children use at school in the UK, this calculation does not work if the answer is really 1. Can anyone explain to me simply... very simply. Thanks
 

topsquark

Forum Staff
Jan 2006
11,602
3,458
Wellsville, NY
Ok I was given this today:

6 - 2 x 4 + 3

Ok so if I use BIDMAS (Brackets Indices Division Multiplication Addition and Subtraction) I get

= 6 - 8 + 3
= 6 - 11
= -5

I was then told the answer was 1 which you get by doing

= 6 - 8 + 3
= -2 + 3
= 1

How come when using BIDMAS rule, which all children use at school in the UK, this calculation does not work if the answer is really 1. Can anyone explain to me simply... very simply. Thanks
Two ways to look at this. Do addition/subtraction from left to right, which is what you did on the second example. The other way is that -8 + 3 is not of the form -(8 + 3). So 6 - 8 + 3 = 6 + (-8) + 3 gives you the right answer as well.

-Dan
 
  • Like
Reactions: Shakarri
Oct 2005
299
1
In other words, the BIDMAS rule which we are taught at school does not apply here and is therefore obsolete?

I mean if you do the addition before the subtraction which its name implies BIDM...AS. Then surely

6 - 2 x 4 + 3
= 6 - 8 + 3
= 6 - 11
= -5
 

topsquark

Forum Staff
Jan 2006
11,602
3,458
Wellsville, NY
In other words, the BIDMAS rule which we are taught at school does not apply here and is therefore obsolete?

I mean if you do the addition before the subtraction which its name implies BIDM...AS. Then surely

6 - 2 x 4 + 3
= 6 - 8 + 3
= 6 - 11
= -5
I'm glad to see that you have the solution. I'll make this comment for the sake of completeness.

What I was trying to say in my earlier post is that the negative on the 8 does not extend to the 3. The simplest way to see this is to "add the opposite of 8":
6 - 2 x 4 + 3 = 6 - 8 + 3 because multiplication comes before the negative.

= 6 + (-8) + 3. Where -8 is the additive inverse of 8.

So either 6 + (-8) + 3 = -2 + 3 = 1
or 6 + (-8) + 3 = 6 - 5 = 1

-Dan
 
Similar Math Discussions Math Forum Date
Pre-Calculus
Similar threads
BODMAS or BIDMAS